Cutaneous pseudolymphoma: a case series of three patients - Yao, Yue; He, Yijia; Wu, Zhuochen; Zhang, Jinfang; Zhang, Guoqiang (Frontiers in Medicine, 2025)
Cutaneous pseudolymphoma is a type of reactive lymphoid hyperplasia that pathologically and/or clinically mimics cutaneous lymphoma. It has a variety of pathogenic factors. However, in many cases, no etiology can be identified. The histopathological findings of cutaneous pseudolymphoma can only be used as the basis for suspected diagnosis. Clinical data, further diagnostic tests and follow-up are needed to confirm the diagnosis. This article reports three cases of cutaneous pseudolymphoma, with different etiology, clinical manifestations and treatment methods. The purpose of this article is to emphasize that the etiology and clinical manifestations of cutaneous pseudolymphoma are diverse, and targeted treatment strategies and long-term follow-up are needed.